2001
DOI: 10.1097/00003226-200110000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Concentrations in Conjunctival Epithelium Brush Cytology Samples Correlate With Neutrophil, Eosinophil Infiltration, and Corneal Damage

Abstract: IL-8 in the extracellular space of the conjunctival epithelium may play a role in the recruitment of neutrophils and possibly eosinophils and in the pathogenesis of corneal damage in severe allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…Moreover, the impression cytology and brush cytology samples can also be used to perform immunohistochemical staining, enzyme-linked immunosorbent assay, flow cytometry, and mRNA expression analysis. 9,10,29,30 Therefore, they are also useful to monitor the pathologic progress in cGVHD-related dry eye disease and helpful for investigating the etiology of cGVHD-related dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the impression cytology and brush cytology samples can also be used to perform immunohistochemical staining, enzyme-linked immunosorbent assay, flow cytometry, and mRNA expression analysis. 9,10,29,30 Therefore, they are also useful to monitor the pathologic progress in cGVHD-related dry eye disease and helpful for investigating the etiology of cGVHD-related dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 They are noninvasive, repeatable, and useful in following the changes in the ocular surface. 8,9 However, there are few reports on impression cytology changes and brush cytology characteristics in patients with cGVHD-related dry eye. 10 On the other hand, the conditioning regimen including total body irradiation and high incidence of meibomian gland dysfunction (MGD) in post-GVHD patients contributes to the ocular surface and tear function changes.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammation was reported as the percentage of inflammatory cells present in the 500 cells counted. 22,24 Quantitative real-time RT-PCR for MUC5AC Quantitative real-time RT-PCR was performed as described previously. 23 Briefly, RNA was extracted from Topical cyclosporine in dry eye in patients with cGVHD Y Wang et al Isogen samples and quantitative real-time PCR was performed according to the manufacturer's instructions (Applied Biosystems, Weiterstadt, Germany).…”
Section: Impression Cytology Parametersmentioning
confidence: 99%
“…It has been reported that the infiltration of inflammatory cells such as mast cells, eosinophils, neutrophils, and T cells were detected in the papillae of VKC patients. [4][5][6][7][8] Therefore, in addition to immunoglobulin E (IgE)-mediated allergy induced by mast cells, a late phase reaction mediated by eosinophils and delayed-type allergy induced by T cells are thought to be involved in VKC induction.Fukushima et al reported the inhibitory effect of CyA eye drops on eosinophil infiltration in a mouse allergic conjunctivitis model. 9) We have also reported that the instillation of CyA inhibited neutrophil infiltration into the conjunctiva in a delayed-type allergic conjunctivitis model in guinea pigs.…”
mentioning
confidence: 99%